2021
DOI: 10.2490/prm.20210009
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of the Mobile Assessment of Varus Thrust Using Nine-axis Inertial Measurement Units

Abstract: Objectives: The purpose of this study was to clarify the diagnostic accuracy of the mobile assessment of varus thrust using inertial measurement units (IMUs). Methods: A total of 80 knees in 49 patients were enrolled in this study. On visual analysis of gait to determine the presence or absence of varus thrust, 23 knees were assigned to the Present group, 17 to the Ambiguous group, and 40 to the Absent group. The peak knee varus angular velocities (PVVs), measured by qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…For gait analysis, IMUs (IMU-Z2, ZMP Inc., Tokyo, Japan) were attached to the waist, both thighs, and both lower legs with straps (Figure 1). As in previous studies, the sampling rate was 100 Hz [15].…”
Section: Gait Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…For gait analysis, IMUs (IMU-Z2, ZMP Inc., Tokyo, Japan) were attached to the waist, both thighs, and both lower legs with straps (Figure 1). As in previous studies, the sampling rate was 100 Hz [15].…”
Section: Gait Analysismentioning
confidence: 99%
“…For gait analysis, IMUs (IMU-Z2, ZMP Inc., Tokyo, Japan) were attached to the waist, both thighs, and both lower legs with straps (Figure 1). As in previous studies, the sampling rate was 100 Hz [15]. The subject walked 10 m three times while wearing an inertial sensor, and the average data were used.…”
Section: Gait Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…As an objective and quantitative method for assessing the degree of VT, the method using inertial measurement units (IMU) has been reported recently [ 34 , 35 , 36 , 37 , 38 ]. A report demonstrated that the index of VT calculated from acceleration and angular velocity data from an IMU attached to the tibia has good test–retest reliability and good discriminative ability for VT [ 38 ].…”
Section: Introductionmentioning
confidence: 99%